2015
DOI: 10.1016/j.tim.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-size maintenance: universal strategy revealed

Abstract: How cells maintain a stable size has fascinated scientists since the beginning of modern biology, but has remained largely mysterious. Recently, however, the ability to analyze single bacteria in real time has provided new, important quantitative insights into this long-standing question in cell biology. In nature, cells can be as small as ∼0.2 mm (e.g., Mycoplasma gallicepticum) and as large as ∼0.1 m (e.g., Syringammina fragilissima), spanning almost six orders of magnitude. Individual organisms, however, sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
211
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(226 citation statements)
references
References 7 publications
10
211
0
Order By: Relevance
“…Indeed, cell size at birth and generation time are weakly correlated negatively (Pearson correlation coefficient, −0.48 ∼ −0.22; SI Appendix, Fig. S12), and this effect must be considered to account for cell size stability (3,(31)(32)(33)(34)(35). Nevertheless, our results suggest that, as far as age-related parameters and population growth rates are concerned, cell size information does not play a predominant role in E. coli over a broad set of culture conditions.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, cell size at birth and generation time are weakly correlated negatively (Pearson correlation coefficient, −0.48 ∼ −0.22; SI Appendix, Fig. S12), and this effect must be considered to account for cell size stability (3,(31)(32)(33)(34)(35). Nevertheless, our results suggest that, as far as age-related parameters and population growth rates are concerned, cell size information does not play a predominant role in E. coli over a broad set of culture conditions.…”
Section: Discussionmentioning
confidence: 82%
“…An important distinction between the current study and previous analyses is the measurement of cell size. In our datasets, cell size was measured via a fluorescent protein-based proxy for cell mass, whereas recent work in bacteria and budding yeast has focused on cell volume [6,[11][12][13]. Elements of cell volume in budding yeast, particularly the vacuoles, are known to undergo dynamic, regulated changes over the course of the cell cycle [39].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a consistent single-cell growth rate across cells, these tenets are sufficient to maintain a consistent size distribution in the population. Recent studies in bacteria have revealed an alternative size control model by which cells add a relatively constant amount of volume over the cell cycle, regardless of their birth size [11][12][13]. Here we use time-lapse microscopy datasets tracking characteristics of individual cells to test these models and further characterize coordination between growth and division in budding yeast.…”
Section: Introductionmentioning
confidence: 99%
“…How this cell-size homeostasis is achieved remains a topic of intense research (6)(7)(8)(9)(10)(11)(12)(13). Recent studies in bacteria propose that rod-shaped bacteria such as Escherichia coli and Bacillus subtilis follow an incremental rule (also known as the ''adder'') (6,7,11,12,14), whereby each cell adds a constant volume to their cell body before dividing. New studies take advantage of technical advancements in microfluidics and live-cell imaging to follow thousands of cell divisions.…”
Section: Introductionmentioning
confidence: 99%
“…Rod-shaped bacteria have fairly constant cell width, which means that cell length may be used as a proxy for size. The increment in cell length before division is independent of cell's length at birth, ruling out alternative size-regulation rules such as the ''timer'', according to which cells would divide at regular intervals, and the ''sizer'', where cells would divide when reaching a maximum size (7,11,12). In a timer model, any noise in the regulatory mechanism would lead to fluctuations in the time of division (Dt), causing the distribution of cell sizes to spread out over consecutive divisions; but that is not the case here.…”
Section: Introductionmentioning
confidence: 99%